Proceedings of the 2018 5th International Conference on Education, Management, Arts, Economics and Social Science (ICEMAESS 201 2018
DOI: 10.2991/icemaess-18.2018.157
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Present Situation of Piano Education in Colleges and Universities

Abstract: To propose some reasonable and scientific teaching methods for piano teaching, the piano teaching of music education majors in comprehensive art colleges was studied. Literature search methods, comparative analysis methods, observation methods, survey methods, and field survey methods were used to study piano teaching. First, the status quo and characteristics of piano teaching were discussed. Second, the way of piano teaching reform was discussed. Third, several suggestions were proposed to improve piano teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Rusticus et al (2023) found that high-quality class environments are associated with students' positive outcomes. Some piano teaching studies have identified the need to improve instruction by selecting appropriate Páginas/ Pages 125-152 Ávila Hernández, Emmanuel; teaching materials, cultivating national music, using effective teaching practices, and developing students' creative and perceptive abilities (Hu, 2018). These results imply that a personalized, suitable, and structured piano environment and effective strategies can benefit learners' progression and help them achieve pianistic objectives.…”
Section: Piano Pedagogy: Influential Factorsmentioning
confidence: 99%
“…Rusticus et al (2023) found that high-quality class environments are associated with students' positive outcomes. Some piano teaching studies have identified the need to improve instruction by selecting appropriate Páginas/ Pages 125-152 Ávila Hernández, Emmanuel; teaching materials, cultivating national music, using effective teaching practices, and developing students' creative and perceptive abilities (Hu, 2018). These results imply that a personalized, suitable, and structured piano environment and effective strategies can benefit learners' progression and help them achieve pianistic objectives.…”
Section: Piano Pedagogy: Influential Factorsmentioning
confidence: 99%